Automatic system of landscape and geophysical data collection - Lagunov, I.M.; Lichak, A.I. (Культура народов Причерноморья, 2001)
The works by I.M.Lagunov (1999) and I.M.Lagunov and A.I.Lychak (1999) described the automatic system of data collection developed as part of the project "Biological efficiency of forest management and environment protection".